Work Engagement of Employees in Moonlighting: A Moderated Mediation Model From a Boundaryless Career Perspective - Peng, Zhen; Wang, Qingsong; Wang, Siwei (Frontiers in Psychology, 2021)
Using a panel of 324 Chinese employees in public sectors, this paper examines the work engagement of employees in moonlighting with the proxy of boundaryless career orientations. We divide work engagement into job engagement and organizational engagement and test their relation to boundaryless career orientations. Results demonstrate that boundaryless career orientations are positively related to job engagement via the mediating effects of role conflicts, and negatively related to organizational engagement through the mediating effects of the relational psychological contracts. Moreover, organizational climate for openness moderates the negative correlation between boundaryless career orientations and role conflicts. There is no significant evidence provided for a moderating effect of organizational climate for openness between boundaryless career orientations and relational psychological contracts.